PENGARUH HUMBLE LEADERSHIP TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI INTRINSIK SEBAGAI VARIABEL MEDIASI PADA PEGAWAI DINAS KOPERASI DAN UKM PROVINSI KALIMANTAN TENGAH - Yolla Anggelina, Rostia; Sambung, Roby; Nur Oktavia, Indah; Eka Damayanti, Nurlia (Penerbit Lafadz Jaya, 2026)
Employee performance in the public sector is a crucial issue in the era of globalization and digitalization. At the Cooperatives and SMEs Office of Central Kalimantan Province, performance issues are reflected in low program realization and limited employee competencies. This research evaluates the influence of humble leadership on employee performance with intrinsic motivation as a mediating variable. Data from employees selected through total sampling technique were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with bootstrapping method. The study also utilized the Upsilon statistical method to quantify the magnitude of mediation effect. According to the study results, the relationship between humble leadership and employee performance was fully mediated by intrinsic motivation. This article presents and analyzes the significance of the results obtained from hypothesis testing and its implications for improving local government employee performance.